Structure Processing Properties Relationships in Stoichiometric and Nonstoichiometric Oxides - Tanasescu, Speranta (IntechOpen, 2020)
The interrelation among composition, microstructure, and properties of stoichiometric and nonstoichiometric compounds is a major field of research for both scientific and technological reasons. As such, this book focuses on metal oxides, which present a large diversity of electrical, magnetic, optical, optoelectronic, thermal, electrochemical, and catalytic properties, making them suitable for a wide range of applications. By bringing together scientific contributions with special emphasis on the interrelations between materials chemistry, processing, microstructures, and properties of stoichiometric and nonstoichiometric metal oxides, this book highlights the importance of tightly integrating high-throughput experiments (including both synthesis and characterization) and efficient and robust theory for the design of advanced materials.